Analisis Penerapan Sistem Informasi Aplikasi Pegadaian Syariah Digital Dalam Memudahkan Nasabah Bertransaksi Menurut Syariah Islam - Rizky Setyaningrum; Siti Afidatul Khotijah (Gorontalo Accounting Journal, 2020)
This study aims to analyze the application of the Pegadaian Syariah Digital information system in facilitating syariah transaction customers at PT. Pegadaian Syariah Ups Mertoyudan. The research method used in this study uses qualitative research throught interviews with customers Pegadaian Syariah Ups Mertoyudan. Then analyzed using descriptive analysis method.The results of this study indicate that the application of Pegadaian Syariah Digital is in accordance with the objectives of Pegadaian Syariah namely to facilitate customers in terms of transactions and provide service that have an impact on customer satisfaction. Pegadaian Syariah Ups Mertoyudan emphasizes the disclosure of detailed and valid information so that it cant prevent wrongdoing in doing business. The application of Pegadaian Syariah Digital in Pegadaian Syariah Ups Mertoyudan is in accordance with islamic syariah principles.